2018
DOI: 10.17977/um033v1i22018p202
|View full text |Cite
|
Sign up to set email alerts
|

Problematik Kompetensi Guru Mata Pelajaran Sejarah di SMKN 1 Jember

Abstract: History teachers have their own problems related to their own competency. This is based on the historical materials acquistion for X grade until XII grade. In this research, the author uses mixed-method research which employs quantitative and qualitative data as the fundamental reference. This research has been done in SMKN 1 Jember and found three problems related to history teachers competency which include the lack of teaches in describing the scope of historical studies, the lack of using historical aids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…First, the learning process that should have been student-centred turns out to be still centred on the teacher who tends to use the lecture method (Pii, 2016). Secondly, because the lecture method emphasises the acquisi-tion of content knowledge, students tend to learn by memorisation (Irani et al, 2018;Sayono, 2013). ird, due to the limitations of primary historical sources that could be utilised for learning purposes (Irani et al, 2018), teachers tend to use textbooks as learning resources for students (Mardiana & Sumiyatun, 2017;Pii, 2016).…”
Section: Planning the Websitementioning
confidence: 99%
“…First, the learning process that should have been student-centred turns out to be still centred on the teacher who tends to use the lecture method (Pii, 2016). Secondly, because the lecture method emphasises the acquisi-tion of content knowledge, students tend to learn by memorisation (Irani et al, 2018;Sayono, 2013). ird, due to the limitations of primary historical sources that could be utilised for learning purposes (Irani et al, 2018), teachers tend to use textbooks as learning resources for students (Mardiana & Sumiyatun, 2017;Pii, 2016).…”
Section: Planning the Websitementioning
confidence: 99%
“…The teaching process that uses textbooks as the main learning resource and is presented through teachers' lectures, culminates in a learning evaluation process that measures students' learning retention in memorizing historical facts that have been presented. Many studies have shown that most students in Indonesia tend to learn history by memorizing the material that has been taught (Irani et al 2018;Sayono 2013). This way of learning could hinder students' historical thinking skills because it does not encourage them to think actively due to the passive reception of information from their teachers and textbooks.…”
Section: Memorizing History: Ritual Knowledgementioning
confidence: 99%
“…First, the learning process that should have been student-centred is still centred on the teacher who tends to use the lecture method (Burhanudin & Sodiq, 2018;Pii, 2016). Secondly, students typically learn by memorisation (Aman, 2019;Irani et al, 2018;Sayono, 2013). Third, due to the limitations of primary historical sources that could be utilised for learning purposes (Irani et al, 2018), teachers tend to only use textbooks as learning resources for their students (Handayani, Basri, & Ekwandari, 2018;Haniah & Rokhman, 2017;Mardiana & Sumiyatun, 2017;Pii, 2016).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Secondly, students typically learn by memorisation (Aman, 2019;Irani et al, 2018;Sayono, 2013). Third, due to the limitations of primary historical sources that could be utilised for learning purposes (Irani et al, 2018), teachers tend to only use textbooks as learning resources for their students (Handayani, Basri, & Ekwandari, 2018;Haniah & Rokhman, 2017;Mardiana & Sumiyatun, 2017;Pii, 2016). Fourth, there are limitations in the use of information and communication technology facilities that are still not optimally utilised by teachers for learning purposes (Agustinova, 2018;Aman, 2019;Mardiana & Sumiyatun, 2017).…”
Section: Background Of the Studymentioning
confidence: 99%
See 1 more Smart Citation